2020
DOI: 10.1044/2019_jslhr-19-00033
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Growth in Single-Word Intelligibility Among Children With Cerebral Palsy From 24 to 96 Months of Age: Effects of Speech-Language Profile Group Membership on Outcomes

Abstract: Purpose We examined whether there were differences among speech-language profile groups of children with cerebral palsy (CP) in age of crossing 25%, 50%, and 75% intelligibility thresholds; age of greatest intelligibility growth; rate of intelligibility growth; maximum attained intelligibility at 8 years; and how well intelligibility at 36 months predicts intelligibility at 96 months when group membership is accounted for. Profile groups were children with no speech motor impairment (NSMI), those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 41 publications
2
27
0
10
Order By: Relevance
“…A second key finding from this study is that intelligibility peaks in its rate of growth at very early ages and that children in lower developmental percentiles tend to be older when they experience their peak in growth rate. The finding that children with lower levels of speech performance experience peak growth later than children with higher levels of performance is generally consistent with findings from our research on children with cerebral palsy (Hustad, Mahr, Broman, & Rathouz, 2020). Interestingly, findings from this study indicate that the 5th percentile of typical children demonstrate peak growth at the same time as children with cerebral palsy who have no evidence of speech motor involvement, providing an important point of convergence for these two groups of children.…”
Section: Rate Of Growthsupporting
confidence: 89%
See 1 more Smart Citation
“…A second key finding from this study is that intelligibility peaks in its rate of growth at very early ages and that children in lower developmental percentiles tend to be older when they experience their peak in growth rate. The finding that children with lower levels of speech performance experience peak growth later than children with higher levels of performance is generally consistent with findings from our research on children with cerebral palsy (Hustad, Mahr, Broman, & Rathouz, 2020). Interestingly, findings from this study indicate that the 5th percentile of typical children demonstrate peak growth at the same time as children with cerebral palsy who have no evidence of speech motor involvement, providing an important point of convergence for these two groups of children.…”
Section: Rate Of Growthsupporting
confidence: 89%
“…In our work on speech intelligibility development in children with cerebral palsy with and without dysarthria, we found that children experienced maximum intelligibility growth between the ages of 36 and 60 months ( Hustad, Sakash, Natzkie, et al, 2019 ). However, for children who had deficits in speech and language ability, results suggested that the age of maximum growth occurred in the later months of this time frame ( Hustad, Mahr, Broman, & Rathouz, 2020 ). To our knowledge, analogous studies have not been performed on typically developing children, so we do not know about growth rates or the timing of peak growth in speech intelligibility.…”
mentioning
confidence: 99%
“…Speech intelligibility in children with dysarthria due to CP is reduced compared to that of typically-developing children (Braza et al, 2019;Hustad et al, 2010;Hustad et al, 2012) and of children with CP with no speech motor impairment (Hustad et al, 2020). Moreover, intelligibility in children with CP with no speech motor deficits is also reduced compared to that of typically developing children (Hustad et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…These difficulties may result in vowel distortions, consonant errors, and difficulty with multisyllabic words (Allison et al, 2017;Bauman-Waengler, 2012). Additionally, children diagnosed with CP, even without dysarthria, have been reported to have reduced intelligibility compared to typically developing peers (Hustad et al, 2019). The genotype of Down syndrome may result in decreased muscle tone of the tongue, lips, soft palate, and jaw (Kumin, 1996;Romski, Sevcik, Barton-Hulsey, et al, 2020).…”
Section: Predictors Of Spoken Language Developmentmentioning
confidence: 99%